PROSES SOLUTION TREATMENT DAN PENGARUHNYA TERHADAP SIFAT MEKANIK DAN STRUKTUR MIKRO PADUAN Zr-Ti-(x)Al PADA APLIKASI SCREW DENTAL IMPLANT - Mulyani, Henny; Nurrobi, Mohamad Iqbal; Prajitno, Djoko Hadi (Jurnal TEDC, 2023)
This research was to investigate the microstructure and mechanical properties of ternary alloys Zr-10Ti-(x)Al (x = 0, 2, 4 wt.%) through solution treatment process with temperature variations 900℃, 1000℃, and 1100℃. The results indicated that α and α' phase existed in Zr-10Ti-(x)Al alloys. The hardness of the Zr-10Ti-4Al alloys in 1100℃ treatment was significantly increased because of solution treatment process, from 382.462 HV (0% Al), 403.304 HV (2% Al), and 465.68 HV (4% Al) to 386.066 HV (0% Al), 452.244 HV (2% Al), and 494.016 HV (4% Al). The addition of Al will increase the hardness of alloy because of strengthening mechanism beside the formation of intermetallic compound, the solution treatment process will increase the percentage of β phase and generated the phase transformation into α' which increased the alloy’ mechanical properties. In conclusion, Zr-10Ti-4Al alloy will be a great potential material for dental implant biomaterial.